2015
DOI: 10.1107/s2052520615013505
|View full text |Cite
|
Sign up to set email alerts
|

Charge density and optical properties of multicomponent crystals containing active pharmaceutical ingredients or their analogues

Abstract: Active pharmaceutical ingredients (APIs), through their favourable donor/acceptor spatial distribution and synthon formation flexibility, are attractive building blocks in modern materials crystallography. The optical properties of a crystal strongly depend on two factors, i.e. the spatial distribution of molecules in the crystal structure and the electronic properties of molecular building blocks (dipole moments, polarizabilities, hyperpolarizabilities). Although the latter are easy to predict through ab init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…The variety of conditions that allowed the recovery of the P­(II) phase demands further studies as no clear correlation was found between the crystallization outcome and the chemical character as well as the physical properties of the used liquids. Additionally in solution the existence of tautomeric forms of barbituric acid is known to influence the cocrystallization processes. , …”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The variety of conditions that allowed the recovery of the P­(II) phase demands further studies as no clear correlation was found between the crystallization outcome and the chemical character as well as the physical properties of the used liquids. Additionally in solution the existence of tautomeric forms of barbituric acid is known to influence the cocrystallization processes. , …”
Section: Results and Discussionmentioning
confidence: 99%
“…Additionally in solution the existence of tautomeric forms of barbituric acid is known to influence the cocrystallization processes. 79,80 Is the reproduction of the P(II) form equivalent to the falsification of its disappearance? In our opinion, based on the provided definition, 29,31 the answer is no.…”
Section: Analysis Of Bomd Simulated H-bondmentioning
confidence: 99%
“…In our previous publications, we have considered sulfonamides as potential building blocks of new crystalline materials (Wojnarska et al, 2018(Wojnarska et al, , 2020). Sulfonamides are one example of APIs which have recently received much attention as the starting components in functional solids (Cherukuvada et al, 2016;Gryl, 2015;Yu et al, 2019;Ji et al, 2020Ji et al, , 2021. The optical materials designed by us were promising as they exhibited large linear birefringence and substantial SHG efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…One component is selected based on its significant molecular hyperpolarizability, while the second one should enforce a polar architecture of a crystal. Recently, active pharmaceutical ingredients (API) have been recognized as useful components of optical materials. , The benefit of active pharmaceutical ingredients’ widespread applications is a large amount of diffraction data useful in the design of new crystalline solids. Isoniazid (INH, pyridine-4-carbohydrazide), a drug used for tuberculosis treatment, is a valuable compound for cocrystallization.…”
mentioning
confidence: 99%
“…Comparing this value with d eff = 0.35 pm/V of commonly used KDP (KH 2 PO 4 ), we can conclude that ( I ) has an SHG efficiency over 6 times better than KDP. Our theoretical methodology was tested in the past on multiple crystalline samples and has proven to give accurate results. ,, In addition to theoretical calculations, SHG measurements were performed using a modified Kurtz–Perry method with a Ti:sapphire pulse laser (MaiTai, Spectra Physics) with excitation wavelengths 800 nm (100 fs) and 1000 nm (100 fs) at a 82 MHz repetition rate. The intensity of backscattered laser light generated by the sample at 400 and 500 nm was measured using a grating spectrograph equipped with a diode array (InstaSpect II, Oriel).…”
mentioning
confidence: 99%